Increased short interval intracortical inhibition in participants with previous hamstring strain injury - Buhmann, R.; Trajano, G. S.; Kerr, G. K.; Shield, A. J. (European Journal of Applied Physiology, 2022)
Purpose Cortical mechanisms may contribute to weakness in participants with previous hamstring strain injury. This study aims to examine intra-cortical inhibition (SICI) and corticospinal excitability in previously injured participants.